Analisis Penilaian Penerapan Bantuan Alat Tangkap Pada Hasil Tangkap Nelayan Pesisir Desa Pahlawan Kecamatan Tanjung Tiram Kabupten Batu Bara - Dewi Mahrani Rangkuty (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2018)
Desa Pahlawan is one of region has natural resources for fishery sectorin Indonesia. The location is in Kecamatan Tanjung Tiram KabupatenBatu Bara Provinsi Sumatera Utara. Many kind of fishery commodityhad produced in there like anchovy, shrimp, shells, and other kind seafood. This research has aim for analyzing the impact for fishing tackleaid implementation for fishermen at Desa Pahlawan KecamatanTanjung Tiram Kabupaten Batu Bara. The research speciality has foranalyzing difference of how before fishing tackle aid implementationand after. The hypothesis are there significant difference betweenbefore fishing tackle aid implementation and after for the quantity ofproduction. The result for this research by sign test has significantdifference between before fishing tackle aid implementation and afterfor the quantity of production. For the local government by DinasKelautan dan Perikanan Kabupaten Batu Bara Provinsi SumateraUtara could be keep the productivity of fishermen at Desa Pahlawan asconcern for quantity of production becauce it can be influence forselling price stability in market as welfare indicator for the fishermen.